1996
DOI: 10.1128/jb.178.1.232-239.1996
|View full text |Cite
|
Sign up to set email alerts
|

A novel alpha-ketoglutarate reductase activity of the serA-encoded 3-phosphoglycerate dehydrogenase of Escherichia coli K-12 and its possible implications for human 2-hydroxyglutaric aciduria

Abstract: Escherichia coli serA-encoded 3-phosphoglycerate (3PG) dehydrogenase catalyzes the first step of the major phosphorylated pathway of L-serine (Ser) biosynthesis. The SerA enzyme is evolutionarily related to the pdxB gene product, 4-phosphoerythronate dehydrogenase, which catalyzes the second step in one branch of pyridoxal 5-phosphate coenzyme biosynthesis. Both the Ser and pyridoxal 5-phosphate biosynthetic pathways use the serC(pdxF)-encoded transaminase in their next steps. In an analysis of these parallel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
129
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(132 citation statements)
references
References 45 publications
(41 reference statements)
3
129
0
Order By: Relevance
“…Enzyme activity was determined by the change in absorbance at 340 nm because of the conversion of NADH to NAD ϩ at pH 7.5 (13) using ␣-ketoglutarate as the substrate (14).…”
Section: Methodsmentioning
confidence: 99%
“…Enzyme activity was determined by the change in absorbance at 340 nm because of the conversion of NADH to NAD ϩ at pH 7.5 (13) using ␣-ketoglutarate as the substrate (14).…”
Section: Methodsmentioning
confidence: 99%
“…Enzyme activity was determined by the change in absorbance at 340 nm due to the conversion of NADH to NAD ϩ at pH 7.5 (18) using ␣-ketoglutarate as the substrate (19).…”
Section: Methodsmentioning
confidence: 99%
“…It has previously been shown that E. coli as well as human phosphoglycerate dehydrogenase can reduce ␣-ketoglutarate (a close structural analog of 3-phosphohydroxypyruvate) to D-2HG in addition to catalyzing their main physiological reaction, which consists of the conversion of 3-phosphoglycerate to 3-phosphohydroxypyruvate in the first step of serine biosynthesis (14,49). Furthermore, in S. cerevisiae, the gene expression profiles of DLD3 and SER33, one of the two yeast phosphoglycerate dehydrogenase isoforms, are highly correlated across several datasets (SPELL version 2.0.3 (50)).…”
Section: Effect Of Modulating Intracellular Yeast Phosphoglycerate Dementioning
confidence: 99%